Implementasi APBN Berkelanjutan di Indonesia: Studi Konseptual dan Empiris - Badiul Hadi (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to explore the concept of a sustainable State Budget (APBN) that supports the achievement of the Sustainable Development Goals (SDGs) in Indonesia. A qualitative approach with a literature study or desk-document method was used to analyze the implementation of sustainable state budgets in various countries. Data was collected through a literature review that included journal articles, policy reports, and official documents from countries that have implemented this principle. The results show that sustainable state budgets must consider environmental, social and economic aspects, and integrate ESG (environmental, social and governance) principles in development planning and budgeting. Some implementation challenges are inter-sectoral coordination, measurement of relevant indicators, and accurate reporting. This study concludes that the application of ESG principles in the state budget and budget policies that support the energy transition can accelerate the achievement of SDGs and ensure future fiscal sustainability.